Epidemiology of compulsorily notifiable diseases in the municipality of Sinop, Mato Grosso, Brazil (Research, Society and Development, 2023)
The present study aimed at the elaboration of an epidemiological profile for the municipality of Sinop-MT and the possible related causal factors. A descriptive study was carried out, with data collected from the Notifiable Diseases Information System (SINAN), on the 10 Notifiable Diseases (CNDs) most reported for the municipality of Sinop-MT for the period 2015-2017, using the filters: Municipality of residence (Sinop), period (2015-2017), sex, age group, case evolution and other most relevant indicators for each condition. When evaluating the main NCDs, it was found that those that occupied the first ten positions regarding the occurrence rate were: dengue, leprosy, domestic, sexual and/or other violence, accident by venomous animals, American cutaneous leishmaniasis, exogenous intoxication, viral hepatitis, infant deaths, AIDS and tuberculosis; which represented around 97.5% of the total notifications. It was found, therefore, that the NCDs, although highly present in Sinop-MT, are presented in a heterogeneous way, which reveals the need for resolute strategies that act in diversified and multifactorial ways and the need for in-depth studies to determine the profile epidemiology within each disease.